2012
DOI: 10.1063/1.4733985
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous structural phase transition properties in ReSe2 and Au-doped ReSe2

Abstract: The high pressure induced phase transition in rhenium diselenides (ReSe(2)) and gold-doped rhenium diselenides (Au-ReSe(2)) at ambient temperature have been investigated using angular-dispersive x-ray diffraction (ADXRD) under high pressure up to around 10.50 and 9.98 GPa, respectively. In situ ADXRD measurements found that the phase transition pressures of ReSe(2) and Au-ReSe(2) began at 9.98 and 8.52 GPa, respectively. Compressibilities analysis shows the relationship of along c-axis > along a-axis > along b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…In the previous work, Hou et al [36] have explored the high-pressure structures of ReS 2 up to 51 GPa using synchrotron x-ray diffraction (XRD), they found an indication of the occurrence of a new high-pressure phase at 11 GPa. Kao et al [37] also found a transition in ReSe 2 at the pressure of 10.5 GPa. However, both of them did not resolve the crystal structure of the high-pressure phases.…”
Section: Introductionmentioning
confidence: 86%
“…In the previous work, Hou et al [36] have explored the high-pressure structures of ReS 2 up to 51 GPa using synchrotron x-ray diffraction (XRD), they found an indication of the occurrence of a new high-pressure phase at 11 GPa. Kao et al [37] also found a transition in ReSe 2 at the pressure of 10.5 GPa. However, both of them did not resolve the crystal structure of the high-pressure phases.…”
Section: Introductionmentioning
confidence: 86%
“…3 One of the most direct ways to probe interlayer interaction is by performing highpressure measurements which allow to directly modulate the interlayer distance. In this regard, high-pressure XRD measurements revealed that ReX2 exhibits the largest compressibility amongst all TMDCs, 30,31 and highpressure Raman measurements on ReS2 showed a twofold decreased pressure coefficient of the out-of-plane A1g phonon mode with respect to other TMDCs. 3 spite the fundamental properties of this crystal system being relatively well known at ambient pressure, high-pressure optical measurements would provide highly valuable information in order to evaluate the degree of electronic interlayer coupling in ReX2.…”
Section: Introductionmentioning
confidence: 94%
“…[2c] Hall measurement indicated a hole mobility ratio of 1.8 between x ‐ and y ‐direction in few‐layered black phosphors, and infrared spectroscopy study revealed anisotropic in‐plane optical photoconductivity from 2 to 5 µm . Beside black phosphorous, ReSe 2 is another representative anisotropic 2D material, which crystallizes in the low symmetry triclinic system and consists of Re 4 diamond shaped chains in the plane . Consequently, electron transport anisotropy ratio of 3.1 was reported for mechanically exfoliated ReSe 2 nanosheets.…”
mentioning
confidence: 99%
“…Angle‐resolved polarized Raman spectroscopy is a powerful tool to diagnose crystal orientation and anisotropic behavior of materials, which has been previously used in anisotropic 2D nanosheets including ReSe 2 [4c] and black phosphorus . Here we thus performed linearly polarized Raman measurements on our 2D Sb 2 Se 3 nanosheets.…”
mentioning
confidence: 99%